Preparation method of iron-based catalyst Fe / CeO2 and application of iron-based catalyst Fe / CeO2 in CO2 catalytic hydrogenation reaction

By regulating the iron load on the nanooctahedral support and preparing the Fe/CeO2 catalyst by deposition-precipitation method, the problems of iron-based catalyst agglomeration and phase transition at high temperatures are solved, high CO generation rate and stability are achieved, and catalytic activity and selectivity are improved.

CN119565621AActive Publication Date: 2025-03-07ANHUI UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411842465.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-07
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

Existing iron-based catalysts are prone to agglomeration, phase transition and carbon deposition at high temperatures and high H2/CO2 ratios, resulting in unstable active site characteristics and insufficient catalytic activity.

Method used

By regulating the iron load on the nanooctahedral support, a highly dispersed Fe/CeO2 catalyst was prepared by deposition-precipitation method to ensure the high dispersion of iron in the catalyst and the stability of the catalyst was improved by calcination treatment.

Benefits of technology

The catalyst was achieved with a high CO generation rate (28.99 mmol CO·gFe-1·s-1) and 150 hours stability at 600°C, which was better than the existing non-precious metal catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119565621A_ABST
    Figure CN119565621A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an iron-based catalyst Fe / CeO2 and application of the iron-based catalyst Fe / CeO2 in CO2 catalytic hydrogenation reaction. Iron is directly introduced onto a Ce (OH) x carrier by adopting a sediment precipitation method, and the prepared Fe / Ce (OH) x material is calcined to generate the Fe / CeO2 catalyst which is used in a reverse water gas shift reaction. Wherein the application of the Ce (OH) x octahedral carrier promotes the dispersion of iron in the preparation of the catalyst. The iron elements highly dispersed on the surface of cerium oxide further promote activation of H2 and adsorption of CO2 in an RWGS reaction through an association reaction path, the CO generation rate of the optimized iron-containing highly-dispersed 1Fe / CeO2 octahedral catalyst is 28.99 mmol COgFe <-1 > s <-1 >, the stability is high when the reaction is performed for 150 h at the temperature of 600 DEG C, and the activity of the catalyst is superior to that of an existing non-noble metal catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of material science and technology, and specifically relates to a highly dispersed, stable and efficient iron-based catalyst Fe / CeO 2 Preparation method and its application in CO 2 Application in catalytic hydrogenation reactions. Background Art

[0002] In recent years, as the greenhouse effect caused by large amounts of carbon dioxide emissions has become increasingly serious, the adverse effects caused by its large-scale emissions have become one of the biggest challenges facing mankind in recent years. An effective way to solve this problem is to chemically convert carbon dioxide into value-added products. In this case, the reverse water gas shift reaction (RWGS) reaction shows many advantages. For example, the reverse water gas shift reaction can realize the conversion and utilization of carbon dioxide, which helps to alleviate the greenhouse effect and reduce carbon emissions. At the same time, carbon monoxide as a product can be reused as a reactant for the production of methanol and hydrocarbons, improving the efficiency of resource utilization. Compared with traditional fossil fuel combustion, the waste gas produced by the reverse water gas shift reaction has a lower carbon dioxide content and has less impact on the environment. In addition, by optimizing the reaction conditions and the use of catalysts, waste gas emissions and energy consumption can be further reduced. The reverse water gas shift reaction has high flexibility and can be adjusted and optimized according to different needs and reaction conditions. For example, by changing the type of catalyst and reaction conditions, the product selectivity and conversion rate can be regulated. In summary, the reverse water gas shift reaction has made significant progress in catalyst research, reaction condition optimization, and application field expansion. Its advantages include high resource utilization efficiency, environmental friendliness, and high flexibility. In the future, with the development of new energy and green chemistry and the continuous advancement of technology, the reverse water gas reaction will be applied and promoted in more fields.

[0003] In the past few decades, researchers have been committed to the facile preparation of high-performance catalysts for the reverse water gas shift reaction (RWGS). 2 The advantages of non-precious metal catalysts in terms of activation and stability during the reaction process are favored. However, non-precious metal catalysts show greater potential for industrial applications, although they each have their own advantages and disadvantages. Copper catalysts show excellent activity at low temperatures, but often face problems of deactivation and structural evolution. The low CO selectivity of nickel-based catalysts is a challenge, and the catalytic activity of molybdenum-based catalysts needs to be further improved. Iron-based catalysts are known for their high performance at high temperatures and complex structures, which can be adjusted by adjusting geometric properties (such as metal dispersion: 15Cu / CeO 2 ; Metal-support interface: 0.5Ir / MoO 3 , KPt / SiO 2 ) and electronic structure (such as Pt 1Fe 1 / CeO 2 、PtNi / ZrO 2 ) to effectively improve the overall performance of RWGS catalysts. Although some progress has been made in the synthesis method, it is still very urgent to develop new non-precious metal catalysts with high catalytic activity, selectivity and thermal stability.

[0004] The application of iron-based catalysts in RWGS reactions has attracted attention due to their thermal stability and low cost, but their catalytic activity is still inferior to that of the most advanced catalysts. Although researchers have achieved different degrees of improvement by adjusting the size, morphology and phase of iron catalysts, the catalytic activity of iron-based catalysts is still poor under high temperature and high H. 2 / CO 2 In contrast, iron-based catalysts are prone to agglomeration, phase change, and carbon deposition, factors that make the nature of the active sites still controversial. Summary of the invention

[0005] In view of the above-mentioned shortcomings of the prior art and the complexity of the structure of the iron-based catalyst, the present invention provides a highly dispersed, stable and efficient iron-based catalyst Fe / CeO 2 Preparation method and its application in CO 2 The invention controls the dispersion and local structure of the iron loading on the nano-octahedron carrier by regulating the iron loading on the nano-octahedron carrier, wherein 1Fe / CeO 2 The CO generation rate of the catalyst at 600 °C can reach 28.99 mmol CO ·g Fe -1 ·s -1 , and showed excellent stability during the 150h stability test.

[0006] The iron-based catalyst Fe / CeO 2 The preparation method adopts a deposition-precipitation method, comprising the following steps:

[0007] Ce(OH) x The carrier was dispersed in deionized water under vigorous stirring, and then 0.01 mol / L ferric nitrate nonahydrate aqueous solution was added dropwise, and the iron loading amount was adjusted by adding the mass of ferric nitrate nonahydrate. Sodium carbonate solution was added to adjust the pH value of the system to 9.0, and the mixture was stirred at room temperature for 2 h, and aged at room temperature for 2 h. The precipitate was filtered, washed with deionized water, and dried continuously at 60 ° C for 12 h. The dried sample was further calcined to obtain the iron-based catalyst Fe / CeO 2 .

[0008] The Ce(OH) x The morphology of the support includes Ce(OH) x Nano-octahedral carrier, Ce(OH) xNanorod support, Ce(OH) x One or more nanocubic carriers, preferably Ce(OH) x Nano-octahedral carrier.

[0009] Furthermore, the Ce(OH) x The nano-octahedral carrier is prepared by a method comprising the following steps:

[0010] 1 mol / L sodium hydroxide solution was added to 5 mol / L cerium nitrate hexahydrate solution (the amount of sodium hydroxide substance: the amount of cerium nitrate hexahydrate substance = 1.4:1), and stirred vigorously for 30 minutes to form a white slurry solution; the mixture was transferred to a Teflon-lined autoclave, and then hydrothermally treated at 175°C for 22-24h. After cooling to room temperature, the precipitate was filtered, washed with deionized water and ethanol, and dried in a vacuum oven at 60°C for 12h to obtain Ce(OH) x Nano-octahedral carrier.

[0011] Furthermore, the Ce(OH) x The nanorod carrier is prepared by a method comprising the following steps:

[0012] 9 mol / L sodium hydroxide solution was added to 5 mol / L cerium nitrate hexahydrate solution (the amount of sodium hydroxide substance: the amount of cerium nitrate hexahydrate substance = 12.6:1), and stirred vigorously for 30 minutes to form a slurry solution; the mixture was transferred to a Teflon-lined autoclave, and then hydrothermally treated at 100°C for 22-24 hours. After cooling to room temperature, the precipitate was filtered, washed with distilled water to a pH of 9.0, and dried in a vacuum oven at 60°C for 12 hours to obtain Ce(OH) x Nanorod carrier.

[0013] Furthermore, the Ce(OH) x The nanocube carrier is prepared by a method comprising the following steps:

[0014] 20 mol / L sodium hydroxide solution was added to 0.08 mol / L cerium nitrate hexahydrate solution (the amount of sodium hydroxide substance: the amount of cerium nitrate hexahydrate substance = 86.9:1), and stirred vigorously for 30 minutes to form a slurry solution; the mixture was transferred to a Teflon-lined autoclave, and then hydrothermally treated at 200°C for 22-24 hours. After cooling to room temperature, the precipitate was filtered, washed with deionized water, and dried in a vacuum oven at 60°C for 12 hours to obtain Ce(OH) x Nanocube carrier.

[0015] Further, the mass of Fe element in ferric nitrate is Ce(OH) x 0.25%-10% of the carrier mass.

[0016] The calcination temperature is 650° C., the holding time is 4 hours, and the heating rate is 5° C. / min.

[0017] The iron-based catalyst Fe / CeO 2 In CO 2 Application in catalytic hydrogenation reactions.

[0018] The specific steps are:

[0019] Step 1: The iron-based catalyst Fe / CeO 2 The product was placed in a reactor, argon was introduced and the temperature was raised to 400°C, and then the atmosphere was switched to pure hydrogen for reduction for 1 hour.

[0020] Step 2: After step 1, the temperature was lowered to 300 °C in an argon atmosphere and a volume ratio of CO was introduced. 2 :H 2 =1:3 raw gas for reaction, and the reaction is carried out at 300-600°C.

[0021] The reverse water-gas shift reaction evaluation device used in the present invention is a fixed bed reactor. The raw gas integration array is composed of carbon dioxide (23%), hydrogen (69%), and nitrogen (8%), and the catalyst loading is 0.01g; the reaction temperature is 300-600℃, and the space velocity is 400000mL·g cat -1 ·h -1 .

[0022] The present invention adopts a hydrothermal method to prepare Ce(OH) in the shape of nanorods, nanocubes and nanooctahedrons. x The support material is used as a carrier to selectively expose different cut surfaces, and based on the strong interaction between the iron nitrate nonahydrate precursor and the surface hydroxyl groups, the iron is directly introduced into the Ce(OH) by the sediment precipitation method. x On the support, the prepared Fe / Ce(OH) x The material is calcined to generate Fe / CeO 2 The catalyst is used in the reverse water gas shift reaction. x The use of octahedral supports facilitates the dispersion of iron in catalyst preparation. These highly dispersed iron elements on the surface of cerium oxide further promote the H in the RWGS reaction through the association reaction pathway. 2 Activation and CO 2 The optimized highly dispersed 1Fe / CeO 2 The CO generation rate of the octahedral catalyst is 28.99 mmol CO •g Fe -1 •s -1, CO selectivity is 100%. It has high stability when reacted at 600℃ for 150h, and its activity is better than that of existing non-precious metal catalysts.

[0023] The present invention has the following effects:

[0024] (1) The catalyst has a simple synthesis method, stable performance, and achieves high dispersion of Fe on nano-octahedral cerium oxide.

[0025] (2) The catalyst adopts the traditional precipitation method to achieve good dispersion of active components, which is beneficial to improving the activity, selectivity and stability of the catalyst.

[0026] (3) The catalyst is cheap and has mild synthesis conditions, which is not only beneficial to reducing the catalyst production cost but also to improving the CO yield in RWGS. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 0.25%-10% Fe / CeO prepared in Example 1 of the present invention 2 When octahedral catalysts are used in RWGS reaction, CO 2 The conversion rate is plotted against temperature.

[0028] Figure 2 0.25%-10% Fe / CeO prepared in Example 1 of the present invention 2 Stability test chart of octahedral catalyst used in RWGS reaction at 600℃ for 20h.

[0029] Figure 3 1Fe / CeO prepared in Example 1 of the present invention 2 Stability test diagram of octahedron used in RWGS reaction at 600℃ for 150h.

[0030] Figure 4 TEM photos of cerium oxide supports with different morphologies prepared in Example 1 of the present invention (Figures a, b and c represent nano-octahedron, nano-rod and nano-cube cerium oxide supports, respectively).

[0031] Figure 5 The Mössbauer spectra of 1.5% Fe loaded on cerium oxide with different morphologies prepared in Example 1 of the present invention (the catalyst with octahedral / rod-shaped / cubic cerium oxide as the carrier is expressed as Fe / CeO 2 -O / R / C, Figure a is 1.5Fe / CeO 2 Mössbauer spectrum of the catalyst, Figure b is the Mössbauer spectrum fitting result parameters).

[0032] Figure 60.25%-10% Fe / CeO prepared in Example 1 of the present invention 2 XRD pattern of catalyst. DETAILED DESCRIPTION

[0033] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.

[0034] Example 1: Preparation of highly dispersed, stable and efficient iron-based RWGS catalyst

[0035] (1) Ce(OH) x Preparation of vector

[0036] Step 1: Add 1 mol / L sodium hydroxide solution to 5 mol / L cerium nitrate hexahydrate solution and stir vigorously for 30 minutes to form a white slurry. Transfer the mixture to a Teflon-lined autoclave and then perform hydrothermal treatment at 175°C for 24 hours. After cooling to room temperature, filter the precipitate, wash it three times with deionized water and ethanol, and dry it in a vacuum oven at 60°C for 12 hours to obtain Ce(OH) x Octahedral carrier ( Figure 4 a).

[0037] Step 2: Add 9 mol / L sodium hydroxide solution to 5 mol / L cerium nitrate hexahydrate solution and stir vigorously for 30 minutes to form a slurry solution. Transfer the mixture to a Teflon-lined autoclave and then perform hydrothermal treatment at 100°C for 24 hours. After cooling to room temperature, filter the precipitate, wash with deionized water to pH 9, and dry in a vacuum oven at 60°C for 12 hours to obtain Ce(OH) x Nanorod carrier ( Figure 4 b).

[0038] Step 3: Add 20 mol / L sodium hydroxide solution to 0.08 mol / L cerium nitrate hexahydrate solution and stir vigorously for 30 minutes to form a slurry solution. Transfer the mixture to a Teflon-lined autoclave and then perform hydrothermal treatment at 200°C for 24 hours. After cooling to room temperature, filter the precipitate, wash it three times with deionized water and ethanol, and dry it in a vacuum oven at 60°C for 12 hours to obtain Ce(OH) x Nanocube carrier ( Figure 4 c).

[0039] (2) Fe / CeO 2 Preparation

[0040] Preparation of Fe / CeO by deposition-precipitation method 2 catalyst.

[0041] The cerium oxide octahedral support was dispersed in deionized water under vigorous stirring. An aqueous solution of ferric nitrate nonahydrate (0.01 mol / L) was added dropwise to the suspension. The iron loading was adjusted by the mass of nitric acid nonahydrate to achieve iron loadings of 0.25%, 0.5wt%, 1%, 1.5%, 3%, 5% and 10wt%. Sodium carbonate solution (0.57 mol / L) was added to keep the pH of the suspension at 9.0. The suspension was stirred for 2 h and aged for 2 h. The precipitate was filtered, thoroughly washed with 1 L of deionized water, and dried at 60 °C for 12 h. The dried sample was further calcined to 650 °C with a heating rate of 5 °C / min and calcined at 650 °C for 4 h, with a loading of 1.5% for nanorod cerium oxide and nanorod cubic cerium oxide Fe.

[0042] Example 2: Fe / CeO 2 Catalyzed Reverse Water Gas Reaction to Produce Synthesis Gas

[0043] The catalyst series prepared in Example 1 were subjected to CO 2 Catalytic hydrogenation activity test. Each catalyst (10 mg, 0.2-0.4 mm) was diluted with 2 g of silicon carbide (0.58-0.8 mm) at atmospheric pressure, and a K-type thermocouple was inserted into the reactor to measure the catalyst temperature. Before the reaction, the catalyst was heated to 400 °C by H 2 In the catalytic activity test, the total gas reaction mixture of 66.7 mL / min, including 23 vol% carbon dioxide, 69 vol% hydrogen and nitrogen balance, corresponds to a GHSV of 400000 mL·g cat -1 ·h -1 The catalysts were heated to 300°C, 400°C, 500°C and 600°C at a heating rate of 10°C / min. The effluent gas was monitored by an online mass spectrometer (Agilent 8860) equipped with a thermal conductivity detector (TCD) to stabilize the catalyst. For stability studies, the catalytic activity of each catalyst was followed within 20 hours after the activity test of the previous catalyst.

[0044] CO 2 The calculation formulas for conversion rate (Formula (1)) and CO selectivity (Formula (2)) are as follows:

[0045] CO 2 conversion(%)=([CO 2 ] In -[CO 2 ] Out ) / ([CO 2 ] In )×100 (1)

[0046] CO selectivity (%) = ([CO] Out ) / ([CO] out +[CH 4 ] Out )×100 (2)

[0047] like Figure 1 and Figure 2 The catalytic performance of the prepared cerium iron oxide octahedral catalyst was evaluated. Before the reaction, the catalyst was heated to 400 °C by H 2 Activation 1h. CO at 300-600℃ and atmospheric pressure 2 / H 2 (1:3) In the gas raw material, the space velocity is 400000mL g cat -1 ·h -1 CO was the only product detected by online gas chromatography during the reaction. Below 400 °C, all Fe / CeO catalysts had low catalytic activity (CO conversion < 3%). At higher reaction temperatures, the CO conversion increased with increasing Fe loading, with Fe loading of 10 wt% for Fe / CeO 2 The maximum conversion rate is 52.26%. The catalytic activity of the blank cerium support at high temperature is negligible, and the highest carbon dioxide conversion rate at 600 ° C is below 5%. 2 Catalytic activity of the catalyst at 600℃ for 20h0.25Fe / CeO 2 、0.5Fe / CeO 2 and 1Fe / CeO 2 The catalytic activity of the high-loaded Fe / CeO 2 The catalytic activity of the catalyst is slightly reduced compared with the currently reported RWGS catalyst. 2 The catalytic activity of the catalyst at 600 °C is 28.99 mmol CO ·g Fe -1 ·s -1 This is significantly higher than the reported iron-based RWGS catalyst (Table 1), and it still has good stability when the reaction time is extended to 150h at 600℃ ( Figure 3 ).

[0048] Preparation of Ce(OH) nanorods, nanocubes and nanooctahedra by hydrothermal method x Support materials. Based on the strong interaction between the iron nitrate nonahydrate precursor and the surface hydroxyl groups, iron was directly introduced into Ce(OH) by a deposition-precipitation method. xThe prepared Fe / Ce(OH) x The material is calcined to produce Fe / CeO 2 The catalyst has an iron loading of 1.5 wt%. The Mössbauer spectra and parameters are as follows Figure 5 As shown. In Fe / CeO 2 Rods and Fe / CeO 2 In the cube, three components were identified. The doublet D1 has an isomeric shift of 0.350 mm / s and a quadrupole splitting of 1.234 mm / s, which can be attributed to iron clusters. The doublet D2 has an isomeric shift of 0.370 mm / s and a lower quadrupole splitting of 0.736 mm / s, which can be attributed to single iron ions, because the more chemical bonds an ion has, the greater the isomeric shift. The sextet has an isomeric shift between 0.372 and 0.380 mm / s and a quadrupole splitting between -0.206 and -0.237 mm / s at a magnetic field of 50.90 T, which can be attributed to larger Fe 2 O 3 Nanoparticles (larger than 10 nm). In Fe / CeO 2 In the octahedral sample, only single Fe ions and clusters were identified, indicating that there is a strong interaction between the support and the metal and that Fe can be highly dispersed during the loading process on the cerium oxide octahedral support. In order to optimize the catalytic performance of the RWGS reaction and further understand the catalytic active sites, the Fe / CeO with different iron loadings were further studied. 2 Octahedral catalyst.

[0049] like Figure 6 As shown, CeO 2 and Fe / CeO 2 Obvious XRD peaks were observed at 2θ=28.46°, 33.01°, 47.39°, 56.29°, 59.05°, 69.34°, 76.69° and 79.01°, respectively, which were attributed to the cubic fluorite structure of CeO 2 (PDF#43-1002). The changes in the diffraction peak positions were negligible. No ferrous oxide, ferric oxide, or ferric oxide phases were detected, indicating that the iron atoms were either incorporated into the cerium lattice or as ultra-small iron oxide particles at the detection limit.

[0050]

Claims

1. A method for preparing an iron-based catalyst Fe / CeO2, characterized in that: Ce(OH) x The carrier was dispersed in deionized water under stirring, and then an aqueous solution of ferric nitrate nonahydrate was added dropwise. The iron loading amount was adjusted by the mass of ferric nitrate nonahydrate added, and a sodium carbonate solution was added to adjust the pH value of the system to 9.

0. The mixture was stirred for 2 h and aged for 2 h. The precipitate was filtered, washed with deionized water, and dried continuously at 60 ° C for 12 h. The dried sample was further calcined to obtain an iron-based catalyst Fe / CeO2.

2. The preparation method according to claim 1, characterized in that: The Ce(OH) x The morphology of the support includes Ce(OH) x Nano-octahedral carrier, Ce(OH) x Nanorod support, Ce(OH) x One or more of the nanocubic carriers.

3. The preparation method according to claim 2, characterized in that: The Ce(OH) x The morphology of the support is Ce(OH) x Nano-octahedral carrier.

4. The preparation method according to claim 2, characterized in that: The Ce(OH) x The nano-octahedral carrier is prepared by a method comprising the following steps: Sodium hydroxide solution was added to cerium nitrate hexahydrate solution and stirred to form a white slurry solution; the mixture was transferred to a Teflon-lined autoclave and then hydrothermally treated at 175°C for 22-24h. After cooling to room temperature, the precipitate was filtered, washed with deionized water and ethanol, and vacuum dried to obtain Ce(OH) x Nano-octahedral carrier.

5. The preparation method according to claim 2, characterized in that: The Ce(OH) x The nanorod carrier is prepared by a method comprising the following steps: Sodium hydroxide solution was added to cerium nitrate hexahydrate solution and stirred to form a slurry solution; the mixture was transferred to a Teflon-lined autoclave and then hydrothermally treated at 100°C for 22-24h. After cooling to room temperature, the precipitate was filtered, washed with distilled water until the pH was 9.0, and vacuum dried to obtain Ce(OH) x Nanorod carrier.

6. The preparation method according to claim 2, characterized in that: The Ce(OH) x The nanocube carrier is prepared by a method comprising the following steps: Sodium hydroxide solution was added to cerium nitrate hexahydrate solution and stirred to form a slurry solution; the mixture was transferred to a Teflon-lined autoclave and then hydrothermally treated at 200°C for 22-24h. After cooling to room temperature, the precipitate was filtered, washed with deionized water, and vacuum dried to obtain Ce(OH) x Nanocube carrier.

7. The preparation method according to claim 1, characterized in that: The mass of Fe in ferric nitrate is Ce(OH) x 0.25%-10% of the carrier mass.

8. The preparation method according to claim 1, characterized in that: The calcination temperature is 650° C., the holding time is 4 hours, and the heating rate is 5° C. / min.

9. Use of the iron-based catalyst Fe / CeO2 prepared according to any one of the preparation methods of claims 1 to 8 in the catalytic hydrogenation reaction of CO2.

10. The use according to claim 9, characterized in that The steps include: Step 1: Place the iron-based catalyst Fe / CeO2 into a reactor, introduce argon gas and heat to 400°C, then switch to pure hydrogen atmosphere for reduction for 1 hour; Step 2: After step 1, the temperature is lowered to 300°C in an argon atmosphere, and a raw material gas with a volume ratio of CO2:H2=1:3 is introduced, and the reaction is carried out at 300-600°C.

Citation Information

Patent Citations

  • Preparation method of platinum-supported catalysts for water gas conversion reaction

    CN103586023A

  • Metal-supported catalyst, preparation method thereof, and application of metal-supported catalyst in plasma catalysis of carbon dioxide hydrogenation to prepare methanol

    CN110560032A

  • Cerium-based catalyst and preparation method thereof

    CN116889878A

  • Catalysts for hydrogen production

    US20060216227A1